Sistemática molecular del complejo Laurencia (Ceramiales, Rhodophyta) en el Caribe mexicano - Díaz Larrea, Jhoana (Universidad Autónoma Metropolitana, 2008)
In the current work the species from the Laurencia complex of the Mexican Caribbean were molecular characterized. Furthermore, the work deals with phylogeny of Laurencia complex and taking into account these phylogenetics relationships, some taxonomic opinions were expressed. To carry out the already mentioned purposes, fresh samples were collected in nine localities through five-hundred kilometers around in the Caribbean coast of the Yucatán peninsula. A total of forty-one samples that includes nine species previously cited as well as the non-identified material were submitted to molecular treatment. The genetic divergence values obtained allow to split the taxonomic categories in specific levels. The highest genetic divergence values were obtained for RUBISCO spacer followed by rbcL. The codon usage for taxa included in grupo externo, Laurencia, Palisada and Osmundea was similar, because of this the mentioned method not allow the groups distinction. The secondary structure comparison allow the clades distinction that corresponding to Palisada and Laurencia genera. The phylogenetics hypothesis based on rbcL, RUBISCO spacer and 18S sequences comparisons corroborated that Laurencia sensu lato is monophyletic and includes three distinct monophyletic clades corresponding to the genera Palisada, Laurencia sensu stricto and Osmundea. Because of this the author conclude that the three genera are distinct units and they don’t correspond to a complex assemblage. The combination of two or more genes in the phylogenetics analyses improve the support of the proposed phylogenetics hypothesis. The analyses with twenty-one coincident taxa to the three genes results in 18S better support and stables topologies. Molecular characters allow to improve the classification scheme of Laurencia sensu lato in intrageneric level. The following taxonomic proposals were made in the current work: two new records for the study zone, Palisada perforata and Osmundea sp; two new combinations, Palisada poiteaui var. gemmifera (Harvey) Sentíes, Fujii et Díaz and Palisada corallopsis (Montagne) Sentíes, Fujii et Díaz; the conspecificity of P. papillosa y P. perforata. The genetic divergence values suggests the existence of a possible new specie in Laurencia genus. In that sense, in the present work we recognize nine taxa for the Mexican Caribbean: five for the Laurencia genus (L. caraibica, L. intricata, L. venusta, L. cf. filiformis and L. sp.), one for Osmundea (O. sp) and four of Palisada genus (P. corallopsis, P. poiteaui var gemmifera, P. poiteaui var poiteaui and P. perforata).; En el presente estudio se caracterizan molecularmente las especies del complejo Laurencia presentes en el Caribe mexicano, se brindan además las posibles relaciones filogenéticas a su interior y se emiten opiniones taxonómicas utilizando como fundamento esta información. Para lograr estos objetivos, material fresco de los distintos taxa fue recolectado en nueve localidades a lo largo de aproximadamente 500 kilómetros del litoral caribeño de la península de Yucatán. Un total de 41 muestras que incluyen a nueve de las especies previamente reportadas así como material que no pudo ser identificado adecuadamente fueron procesadas para la obtención de ADN. Los valores de divergencia genética en los tres genes permitieron segregar categorías taxonómicas a nivel específico. Los mayores valores de divergencia se obtuvieron para la región espaciadora y rbcL. El uso del codón en los taxa que conforman el grupo externo, Laurencia, Palisada y Osmundea fue similar, por tanto no permitió la segregación de dichos grupos. La comparación de las estructuras secundarias permitió la distinción de los clados pertenecientes a los géneros Palisada y Laurencia. Las hipótesis filogenéticas generadas a partir de secuencias parciales de los genes rbcL y RUBISCO del cloroplasto y 18S nuclear confirman que Laurencia sensu lato es monofilético y que en él se incluyen tres clados que corresponden a los géneros: Laurencia sensu stricto, Palisada y Osmundea, todos ellos también monofiléticos, lo que nos lleva a concluir que estas unidades son independientes y en términos taxonómicos no pueden corresponder a una agrupación de complejo. La combinación de dos ó más genes en los análisis filogenéticos respaldan con mayor fortaleza las relaciones postuladas. En los análisis realizados con 21 taxa comunes a los tres genes, las topologías más estables y mejor resueltas se obtuvieron con las secuencias de 18S. Los caracteres moleculares permitieron hacer modificaciones al esquema de clasificación de Laurencia sensu lato a nivel intragenérico. Se proponen dos nuevos registros para la zona de estudio: Palisada perforata y Osmundea sp. Se plantean dos combinaciones nuevas: Palisada poiteaui var. gemmifera (Harvey) Sentíes, Fujii et Díaz y Palisada corallopsis (Montagne) Sentíes, Fujii et Díaz. Así como la conespecificidad de P. papillosa y P. perforata. Los datos de divergencia genética sugieren la existencia de una posible especie nueva para la ciencia en el género Laurencia. De esta manera en el presente trabajo se reconocen como presentes en el Caribe mexicano cinco taxa de Laurencia (L. caraibica, L. intricata, L. venusta, L. cf. filiformis y L. sp.), uno de Osmundea (O. sp) y cuatro de Palisada (P. corallopsis, P. poiteaui var gemmifera, P. poiteaui var poiteaui y P. perforata).